2016
DOI: 10.1002/anie.201509920
|View full text |Cite|
|
Sign up to set email alerts
|

A Unique Tryptophan C‐Prenyltransferase from the Kawaguchipeptin Biosynthetic Pathway

Abstract: Cyanobactins are a rapidly growing family of linear and cyclic peptides produced by cyanobacteria. Kawaguchipeptins A and B, two macrocyclic undecapeptides reported earlier from Microcystis aeruginosa NIES-88, are shown to be products of the cyanobactin biosynthetic pathway. The 9 kb kawaguchipeptin (kgp) gene cluster was identified in a 5.26 Mb draft genome of Microcystis aeruginosa NIES-88. We verified that this gene cluster is responsible for the production of the kawaguchipeptins through heterologous expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 33 publications
2
65
0
Order By: Relevance
“…For example, representative members of the indole alkaloid ABBA prenyltransferase family catalyze the regioselective normal or reverse prenylation of a variety of natural products . The KgpF, SirD, and PagF prenyltransferases from the kawaguchipeptin, sirodesmin PL, and prenylagaramide biosynthetic pathways, respectively, have all demonstrated substrate promiscuity in vitro . Such broad substrate specificity could be expected to facilitate the spread and integration of these enzymes into new natural product biosynthetic pathways.…”
Section: Horizontal Gene Transfer Facilitates the Distribution Of Natmentioning
confidence: 99%
“…For example, representative members of the indole alkaloid ABBA prenyltransferase family catalyze the regioselective normal or reverse prenylation of a variety of natural products . The KgpF, SirD, and PagF prenyltransferases from the kawaguchipeptin, sirodesmin PL, and prenylagaramide biosynthetic pathways, respectively, have all demonstrated substrate promiscuity in vitro . Such broad substrate specificity could be expected to facilitate the spread and integration of these enzymes into new natural product biosynthetic pathways.…”
Section: Horizontal Gene Transfer Facilitates the Distribution Of Natmentioning
confidence: 99%
“…11 By contrast, related prenyltransferases are known to prenylate the side-chains of amino acids within macrocyclic peptides. 1215 Likewise, enzymes that are known to exclusively methylate the α-carboxylate on peptides have not been characterized. Here, we provide biochemical characterization supporting these proposed functions of AgeMTPT.…”
mentioning
confidence: 99%
“…Sequencing of the producing strain suggested that both of the products are RiPPs that are produced by a single cyanobactin pathway, which was confirmed by heterologous expression of the constituent genes in E. coli (Parajuli et al, 2016). A single enzyme, KgpF, functions on a range of cyclic and linear peptide substrates and prenylates C3 on the amino acid tryptophan, which is a unique modification in RiPP products.…”
Section: Prenyltransferasesmentioning
confidence: 85%
“…The prenyltransferases are known to prenylate in either the forward or reverse orientation in respect to DMAPP. TruF is specific to serine and threonine O -prenylation (Donia et al, 2008; Sardar, Lin, & Schmidt, 2015; Tianero, Donia, Young, Schultz, & Schmidt, 2012; Tianero et al, 2016), while other variants prenylate tyrosine (Hao et al, 2016; McIntosh, Donia, Nair, & Schmidt, 2011; McIntosh, Lin, Tianero, & Schmidt, 2013) or tryptophan (Parajuli et al, 2016). While each prenyltransferase appears to be relatively selective for the amino acid, orientation, and isoprene donor, there is much less selectivity as far as peptide structure, and no known associated RS (Hao et al, 2016; McIntosh et al, 2011).…”
Section: Biosynthetic Diversity Of the Cyanobactin Familymentioning
confidence: 99%
See 1 more Smart Citation